ByzRev 03.2021.034: James T. Chlup – Conor Whately (eds), Greek and Roman Military Manuals. Genre and History: (Routledge Monographs in Classical Studies). London – New York: Routledge Taylor & Francis Group 2020. - Rance, Philip (The Byzantine Review, 2021)
James T. Chlup – Conor Whately (eds), Greek and Roman Military Manuals. Genre and History (Routledge Monographs in Classical Studies). London – New York: Routledge Taylor & Francis Group 2020. xi, 295 pp. – ISBN 978-1-13833514-1